2021
DOI: 10.47292/joint.v3i2.63
|View full text |Cite
|
Sign up to set email alerts
|

Pemilihan Lokasi Awal Usaha Bagi Usaha Mikro Kecil Dan Menengah Dengan Metode Analitycal Hierarchy Process

Abstract: Usaha Mikro Kecil dan Menengah (UMKM) merupakan ekonomi produktif yang berdiri sendiri yang dilakukan oleh perorangan atau badan usaha. Permasalahan yang muncul adalah calon pelaku UMKM memiliki kriteria tersendiri mengenai lokasi ideal sesuai kriteria yang diinginkan sehingga penentuan lokasi akan bersifat subjektif dan menghasilkan berbagai kemungkinan. Untuk dapat menyelesaikan masalah tersebut pada penelitian ini diusulkan penggunaan metode AHP sebagai media hitung multikriteria agar dapat menghasilkan ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The criteria involved in study consist of four main criteria, namely population, competition, retail settlement, and costs (Akalin, Turhan, et al, 2013). The study by Adhiarta, Witanti, et al (2021) for selecting initial business locations for micro, small and medium enterprises by using AHP method listed the criteria that affected the selection of the locations: environment, accessibility, and facilities. They also come to the conclusion that businessmen need to know and consider the criteria that can support their business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The criteria involved in study consist of four main criteria, namely population, competition, retail settlement, and costs (Akalin, Turhan, et al, 2013). The study by Adhiarta, Witanti, et al (2021) for selecting initial business locations for micro, small and medium enterprises by using AHP method listed the criteria that affected the selection of the locations: environment, accessibility, and facilities. They also come to the conclusion that businessmen need to know and consider the criteria that can support their business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One element absolutly most important than others 2, 4,6,8 The values between two considerations Source: (Saaty, 2001)…”
Section: Table 1 Scale Of Pairs Comparison Value Intensity Criteriamentioning
confidence: 99%
“…Based on research in journal entitled "Selection of Initial Business Locations for Micro, Small and Medium Enterprises Using the Analytical Hierarchy Process Method" concluded that: business people need to see and consider what criteria can support the business. There are criteria used to be used as business land such as the location must be clearly visible, the location is in a crowded place, the location must have easy access, the location is close to the target market and pay attention to competitors in that location [4].…”
Section: Relevant Researchmentioning
confidence: 99%
“…Business location is one of the elements that plays an important role in supporting business continuity. Location is the place for every business and is an important decision, as a wrong decision can result in failure before the business starts (Rija, 2018;Adhiarta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%